2021
DOI: 10.2147/ijgm.s322359
|View full text |Cite
|
Sign up to set email alerts
|

Is Prenatal Diagnosis Necessary for Fetal Isolated Nasal Bone Absence or Hypoplasia?

Abstract: Purpose This study aimed to explore the value of chromosomal microarray analysis (CMA) and whole exome sequencing (WES) in the prenatal diagnosis of fetal isolated nasal bone absence (INBA) or isolated nasal bone hypoplasia (INBH). We hope to provide additional relevant information for clinical counseling. Patients and Methods From November 1, 2018, to March 1, 2020, 55 pregnant women with isolated nasal bone dysplasia were admitted to the Changzhou Maternity and Child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 31 publications
0
17
1
Order By: Relevance
“…The second limitation is the lack of autopsy and Cleidocranial dysplasia (MIM 119600) is characterized by hypoplastic/aplastic clavicles, a brachycephalic skull, midfacial hypoplasia with a low nasal bridge, abnormal tooth development and other skeletal abnormalities. Prenatal diagnosis of cleidocranial dysplasia has been described in several reports [11,25]. Chen et al described a case of cleidocranial dysplasia, associated with nasal bone hypoplasia; the fetus demonstrated mild shortness of the femur and absence of a nasal bone at 22-and 31-weeks gestation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second limitation is the lack of autopsy and Cleidocranial dysplasia (MIM 119600) is characterized by hypoplastic/aplastic clavicles, a brachycephalic skull, midfacial hypoplasia with a low nasal bridge, abnormal tooth development and other skeletal abnormalities. Prenatal diagnosis of cleidocranial dysplasia has been described in several reports [11,25]. Chen et al described a case of cleidocranial dysplasia, associated with nasal bone hypoplasia; the fetus demonstrated mild shortness of the femur and absence of a nasal bone at 22-and 31-weeks gestation.…”
Section: Discussionmentioning
confidence: 99%
“…After excluding trisomy 21, the incidence of CNV in this group was 7.4%. In addition, monogenic diseases were diagnosed in two other cases: cleidocranial dysplasia and Sifrim-Hitz-Weiss syndrome [ 11 ]. In our study, out of the three abnormal CMA results, one was a variant of unknown significance and one was potentially pathogenic.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of fetuses presenting isolated and non-isolated genitourinary anomalies, the diagnostic rate was 12% [235], whereas in another paper, the diagnostic rate was 7% [237]. In one recent paper analyzing fetuses with isolated hypoplastic/absent nasal bone, the diagnostic rate was 17% [277] (Table S4). Concerning IFs, 6 of the selected papers in Group A and 14 papers in Group B explicitly reported IFs (Tables S3 and S4).…”
Section: Exome Sequencingmentioning
confidence: 97%
“…In contrast, Gu et al. reported their tertiary-centre experience with isolated hypoplastic NB and found a non-trisomy-21 abnormality in 2 of the 39 foetuses, resulting in a frequency of pathogenic CNVs in isolated hypoplastic NB of 5.1% [ 15 ]. Du et al.…”
Section: Discussionmentioning
confidence: 99%
“…studied 80 cases of isolated hypoplastic foetal NB and showed no cases of pathogenic copy number variations (CNVs) detected [ 14 ]. However, recent study with small sample size reported that the rate of pathogenic CNVs was 5.45% (3/55) in the foetuses with isolated absence or hypoplasia NB [ 15 ]. As a result, should CMA be offered to isolated absent or hypoplastic foetal NB remain unclear.…”
Section: Introductionmentioning
confidence: 99%